QUALITY OF LIFE IN WOMEN VICTIMS OF THE ARMED CONFLICT BETWEEN 2019 AND 2020 - Romero-Jiménez , Mónica Liliana
In Colombia, the female population victims of the armed conflict have been one of the most affected by the consequences generated by violence and the different types of attacks to which they have been subjected. In accordance with this, the present quantitative descriptive article aims to identify the quality of life of women victims of the armed conflict from the variables of physical and psychological health, social relationships, and environment. This through the development of solidarity actions carried out by students of the National Open and Distance University (UNAD) who are studying the Unadista Social Service Provision (SISSU). For which a sample of 223 women from different regions of Colombia was taken and the WHOQOL-BREF Quality of Life Scale of the World Health Organization was applied, which contemplates measuring the quality of life from these four dimensions. Among the general results, it is identified that interpersonal relationships and with the environment are the main factors that are most affected in the quality of life, likewise, women who have a higher educational level consider that their quality of life in relation to the psychology domain is better.